Scaphoid screw placement under minimal radiation exposure. (November 2017) - Hohenberger, Gloria M.; Berzins, Uldis; Bakota, Bore; Holweg, Patrick; Clement, Bernhard; Grechenig, Stephan
Abstract: Background: Percutaneous scaphoid fixation through either a volar or dorsal approach has the advantage of minor soft tissue damage compared with ORIF, and faster fracture union compared with conservative treatment. However, this technique demands highly intraoperative reliance on X-ray control, including increased radiation exposure and all associated side effects. Purpose: To test the possibility and efficacy of volar percutaneous scaphoid screw placement under minimalradiation exposure. Methods: The sample included 20 hands (seven left, 13 right) from human adult cadavers. For this study, the utilised wrists were assumed to have non-displaced scaphoid fractures. Using a percutaneous approach, a 2-mm Kirschner wire (K-wire) was advanced to the distal pole of the scaphoid and placed in a 45° horizontal and vertical angle under monitoring with the C-arm. The K-wire was inserted blindly alongside the estimated length of the scaphoid. Following K-wire insertion, four X-rays were taken to depict K-wire positioning and to assess positioning alongside the axis of the scaphoid and K-wire protrusion. The rating scale comprised 1 (good), 2 (moderate) or 3 (poor). Results: All tested radiographic views were evaluated with a median of 2 points (moderate position) regardingplacement alongside the scaphoid axis. Conclusion: Our results indicate that percutaneous scaphoid fixation with the guide wire placed in a 45° horizontal and vertical angle enables primary moderate positioning, which may lead to quicker adjustment to the ideal position and a decrease of radiation exposure.